Tren Baru Islam melalui Gerakan Hijrah: Studi Kasus Shift Pemuda Hijrah - Paelani Setia; Rika Dilawati (UIN Sunan Gunung Djati Bandung, 2021)
This article aims to discuss the strategy of the hijrah movement in utilizing the hijrah trend in urban areas. This study takes a case study on the religious youth movement, the Youth Hijrah Movement (Shift) in Bandung City, in actualizing Islamic values that are packaged in a contemporary way according to the millennial generation. The research method used is qualitative by exploring understanding and responses through interviews with administrators, members, and congregations regarding Shift's contribution in spreading Islam conventionally and through social media platforms. The results of this study state that Shift takes advantage of the trend of migration due to the phenomenon of urban youth spirituality drought through interesting and useful religious programs for the wider community. The Shift is a manifestation of the existence of a Cyber Islamic Environment or an Islamic cyber environment in cyberspace that is used to convey Islamic messages. The activities of the Shift movement that are packaged on social media platforms and their interactions with the congregation are the new face of Islam in cyberspace. In addition, to accommodate traditional religious traditions such as Islamic boarding schools, the Shift also makes symbolic efforts to use its learning methods like an Islamic boarding school.